Healthcare decision-makers’ perspectives on evaluating conflict management training in paediatric healthcare: a utilisation-focused qualitative study - Oscar Lyons; Sarah Barclay; Esse Menson; Juliette Phillipson (BMJ Paediatrics Open)
Background Conflict is prevalent across healthcare settings but is especially common in paediatrics, where high emotional stakes and parental expectations often intensify disagreements. Conflict can lead to negative outcomes for hospitals, staff and patients. Effective conflict management training can mitigate these impacts, but evaluating such training programmes remains challenging due to a lack of standardised tools and best practices.Methods This qualitative study aimed to explore healthcare decision-makers' perspectives on what key areas should be evaluated in conflict management training programmes in paediatric healthcare settings, employing Patton’s utilisation-focused evaluation approach. Semi-structured interviews were conducted with 13 healthcare decision-makers and key stakeholders from various healthcare and charitable organisations. Interviews were analysed using reflexive thematic analysis by Braun and Clarke to identify key themes for evaluation.Results Four primary themes were generated regarding the key areas that healthcare decision-makers believe should be evaluated in conflict management training. These were experience of training sessions, staff competency and well-being, patient/family experiences of conflict and impact on staff time and on clinical resources. Interviewees identified that the evaluation of training sessions should focus on participant engagement and satisfaction. Codes relating to staff competency and well-being included the acquisition and long-term retention of conflict management skills. Codes relating to patient/family experience focused on the quality of communication and support during conflicts. The theme of resource utilisation included codes relating to the time and cost implications of conflict.Conclusion The study identified essential evaluation areas that align with and expand on Kirkpatrick’s framework, suggesting the need for both qualitative and quantitative data and long-term follow-up. Tailoring evaluation frameworks to specific programme contexts can enhance their relevance and utility, contributing to improved conflict management in both paediatric and wider healthcare settings.